-5=6(3)-27

Simple and best practice solution for -5=6(3)-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5=6(3)-27 equation:


Simplifying
-5 = 6(3) + -27

Multiply 6 * 3
-5 = 18 + -27

Combine like terms: 18 + -27 = -9
-5 = -9

Solving
-5 = -9

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 25x^4-60c^2+36=0 | | 2/x-3=8/3x-3 | | 3=6(-5)-27 | | (12a^2b^-2)/(8a^-3b^7) | | 5x+4=x-20 | | 12a^2b^-2/8a^-3b^7 | | logx=-.29 | | a=84+2(10) | | 15n-1+5=0 | | a=54+5(10) | | a=84+2(1000) | | .6c+11=5 | | a=54+5(1000) | | 2(y-5)=4y+10 | | 1/2•6 | | a=54+5(5) | | 6c-7=17 | | y-b=kx | | A=84+2(20) | | 6(7x+1)=43 | | y-b/k=kx/k | | 1.25(x+75)=250 | | 4x-(3x+15)=30 | | A=54+5(20) | | 5k^2=3-2k | | 3x-9x=21 | | 2.4e+12= | | 8=4n-16 | | 2x+7=-3x+17 | | 9x+4x-x=48 | | 72=-12r+96 | | -5(v-7)(-v+8)=0 |

Equations solver categories